2021
DOI: 10.1182/blood-2021-149784
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is a Clinically Relevant and Independent Predictor of Health Outcomes after Chimeric Antigen Receptor T-Cell Therapy for Lymphoma

Abstract: Introduction: Chimeric antigen receptor T cell (CAR-T) therapy is an effective treatment for patients with relapsed/refractory diffuse large B cell lymphoma (DLBCL) or other B-cell lymphomas. However, the potent anti-lymphoma effect of CAR-T is balanced by the risk of acute toxicities, namely cytokine release syndrome (CRS) and Immune effector cell-Associated Neurotoxicity Syndrome (ICANS), as well as the variable length of progression-free survival (PFS) after CAR-T. Tools to better risk-stratify for adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…CT body composition was performed using the data analysis tool (DAFS) developed by the co-authors. DAFS has been reported and shown to be highly accurate in different malignancies such as esophageal cancer and lymphomas 20 , 21 . The use of a fully automated algorithm for assessing an endocrine-related malignancy is a novel use and application of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…CT body composition was performed using the data analysis tool (DAFS) developed by the co-authors. DAFS has been reported and shown to be highly accurate in different malignancies such as esophageal cancer and lymphomas 20 , 21 . The use of a fully automated algorithm for assessing an endocrine-related malignancy is a novel use and application of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Upper GI comorbidities, for example, could lead to poor nutrition, weight loss, and muscle mass depletion (ie, sarcopenia), which has been associated with poor CART outcomes. 42 Renal comorbidities could predispose to renal failure or impaired medication clearance, thus leading to additional toxicity. A recent RWE study found that recipients of CART who had compromised renal function at baseline had longer intensive care unit stays and higher rates of early nonrelapse mortality (19.5% vs 8.3% at 3 months).…”
Section: Discussionmentioning
confidence: 99%